The Ottoman twilight in the Arab lands : Turkish testimonies and memories of the Great War - Deringil, Selim, 1951- (Turkish and Ottoman studies., 2019)
The Great War is still seen as a mostly European war. The Middle Eastern theater is, at best, considered a sideshow written from the western perspective. This book fills an important gap in the literature by giving an insight through annotated translations from five Ottoman memoirs, previously not available in English, of actors who witnessed the last few years of Turkish presence in the Arab lands. It provides the historical background to many of the crises in the Middle East today, such as the Arab-Israeli confrontation, the conflict-ridden emergence of Syria and Lebanon, the struggle over the holy places of Islam in the Hejaz, and the mutual prejudices of Arabs and Turks about each other.